The Influence of Brand Equity, Lifestyle, and Reference Group on Purchasing Decisions for Eiger Products for Students - Anugrah Romadhoni; Arini Hidayah; M Agung Miftahuddin; Suyoto Suyoto (Trescode Green Organization, 2025)
This study aims to determine the effect of brand equity on purchasing decisions, lifestyle on purchasing decisions, reference groups on purchasing decisions. The data analysis technique in this study uses the Structural Eqquittion Modeling (SEM) method and the analysis tool uses the SmartPLS version 4.0 application. The population in this study were students of Muhammadiyah Purwokerto University. The sampling technique used purposive sampling technique. The sample used in this study was 100 respondents determined by the slovin formula. The results showed that brand equity has a positive and significant effect on purchasing decisions, lifestyle has a positive and significant effect on Purchasing Decisions, Reference Group has a positive and significant effect on Purchasing Decisions. The implication of this research is that businesses and marketers targeting students of Muhammadiyah Purwokerto University should focus on strengthening brand equity, understanding lifestyle preferences, and leveraging the influence of reference groups to effectively enhance purchasing decisions.